(untitled) (Andamios, Revista de Investigación Social, 2016)
Changes in the media landscape and the digital and multimedia environment require new directions in the way journalism is trained. This research aims to understand to what extent Portuguese and Spanish universities have used the implementation of the Bologna Declaration by European Union countries as an opportunity to restructure journalism curricula, especially regarding technological and digital contents. The results show an increasing number of courses devoted to digital/ technological contents. Besides, there is a wide variety of denominations. These courses comprise more generic contents (related to digital and technological issues) but also subjects specifically devoted to journalism practice. These results allow us to trigger a discussion on the journalism training strategy that may be involved in these curricular options.